2014
DOI: 10.1007/s13593-014-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology in agriculture, livestock, and aquaculture in China. A review

Abstract: Nanoscience emerged in the late 1980s and is developed and applied in China since the middle of the 1990s. Although nanotechnologies have been less developed in agronomy than other disciplines, due to less investment, nanotechnologies have the potential to improve agricultural production. Here, we review more than 200 reports involving nanoscience in agriculture, livestock, and aquaculture. The major points are as follows: (1) nanotechnologies used for seeds and water improved plant germination, growth, yield,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
132
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(136 citation statements)
references
References 95 publications
1
132
0
3
Order By: Relevance
“…Image modified from Prasad et al (2012), Raliya and Tarafdar (2013), and Servin et al (2015a), with permission micronutrients, so that they accumulate, are redistributed, and solubilized inside plant tissues, as shown for Cu, Zn, and also Mg (Dimkpa et al 2012b(Dimkpa et al , 2013aWang et al 2012aWang et al , b, 2013aLv et al 2014). Nanofertilizers are already used in crop production in China, but reported only for urea (Huang et al 2015), and should therefore be extended to micronutrients. Nanopackaging can be leveraged to reduce nutrient losses to the environment (Huang et al 2015;Liu and Lal 2015), which is characteristic of nutrients administered as soluble salts.…”
Section: Some Ways Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…Image modified from Prasad et al (2012), Raliya and Tarafdar (2013), and Servin et al (2015a), with permission micronutrients, so that they accumulate, are redistributed, and solubilized inside plant tissues, as shown for Cu, Zn, and also Mg (Dimkpa et al 2012b(Dimkpa et al , 2013aWang et al 2012aWang et al , b, 2013aLv et al 2014). Nanofertilizers are already used in crop production in China, but reported only for urea (Huang et al 2015), and should therefore be extended to micronutrients. Nanopackaging can be leveraged to reduce nutrient losses to the environment (Huang et al 2015;Liu and Lal 2015), which is characteristic of nutrients administered as soluble salts.…”
Section: Some Ways Forwardmentioning
confidence: 99%
“…Nanofertilizers are already used in crop production in China, but reported only for urea (Huang et al 2015), and should therefore be extended to micronutrients. Nanopackaging can be leveraged to reduce nutrient losses to the environment (Huang et al 2015;Liu and Lal 2015), which is characteristic of nutrients administered as soluble salts. Moreover, by providing alternative uptake pathways through the internalization of intact particles, ionic nutrient competition could be circumvented during uptake from shared pathways.…”
Section: Some Ways Forwardmentioning
confidence: 99%
“…Nanomaterials hold great promise of improved plant disease resistance, controlled release of agro-chemicals, enhanced plant growth, etc [12]. According to Taha (2016), nanomaterials can be used as a magical tool for enhancing growth and improvement of agricultural production [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology, the engineering of functional systems at the molecular scale, has been focused on the manufacturing industry, but it has also been applied in medicine as agents for in vitro detection, in vivo diagnostics, multimodal imagining, chemotherapy, phototherapy, and immunotherapy (Giasuddin et al, 2013;Lin, 2015). Moreover, in agriculture activities it has been pointed out that nanometric biological pesticides poses higher efficiency and present lower cost than regular pesticides, offering a reliable choice (Huang et al, 2015). On the other hand, in the application of nanosciences in aquaculture production Khalafalla et al (2011) reported that selenium nanoparticles could improve reproduction, growth, and survival of Oreochromis niloticus.…”
Section: _____________________mentioning
confidence: 99%
“…Some nanoparticles may have antibacterial activity, and affect many species of bacteria (Lu et al, 2013;Huang et al, 2015;Bakare et al, 2016). For example, copper nanoparticles have been proved as promising antibacterial agents against the intestinal bacteria Aeromonas hydrophila, Vibrio parahaemolyticus, and Pseudomonas fluorescens in silver and grass carp (Huang et al, 2015), and Kim et al (2007) reported that the use of silver nanoparticles (AgNPs) inhibited the growth of yeast, Escherichia coli (Escherich), and Staphylococcus aureus (Rosenbach).…”
Section: _____________________mentioning
confidence: 99%